The Implementation of Supervision Standard Policy at MAN 1 Musi Banyuasin - Sumiyati, Sumiyati; Widayatsih, Tri; Eddy, Syaiful (Journal of Social Work and Science Education, 2023)
This study investigates how the standard policy of educational supervision is implemented in MAN 1 Musi Banyuasin. This research will be carried out for 5 (five) months, including the design, implementation, and reporting of research findings. This study’s design employs descriptive qualitative methods, which include prioritizing data research or the reality of the problem based on the disclosure of what has been explored and disclosed by respondents in the form of interview results and data collected in the form of words. The study’s findings revealed that the implementation of the Standard Supervision Policy at MAN 1 Musi Banyuasin on the Communication indicator as a whole went very well. Running but not optimal on the resource indicator. The Disposition indicator remains rigid and ineffective. The bureaucratic structure indicator was not implemented properly, so it did not work.